2022
DOI: 10.1055/s-0042-1755721
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Intestinal Ischemia in A 7-Year Old Boy

Abstract: Severe abdominal pain and vomiting are common symptoms in children with pediatric multisystem inflammatory syndrome (PIMS). Mesenteric lymphadenitis and aseptic peritonitis are predominantly reported in cases where acute surgical abdomen was suspected and laparotomy was performed at the early stage of the pandemic. These reports generally discouraged surgeons to perform exploration in COVID-19-related cases and medical management was prioritized. Only a few COVID-19-specific surgical cases with intestinal isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(28 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…Subsequently, 103 articles remained, which were analyzed in full text. In total, 34 studies met our inclusion criteria and reported SARS-CoV-2 infection in pediatric patients with ISN and were included for systematic review and meta-analysis [ 4 , 5 , 6 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The detailed characteristics of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, 103 articles remained, which were analyzed in full text. In total, 34 studies met our inclusion criteria and reported SARS-CoV-2 infection in pediatric patients with ISN and were included for systematic review and meta-analysis [ 4 , 5 , 6 , 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The detailed characteristics of the included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the included studies are shown in Table 1 . There were 28 case report [ 4 , 6 , 7 , 15 , 16 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], 5 cohort [ 20 , 34 , 42 , 43 , 44 ] and 1 case-series [ 5 ] studies. These studies were conducted in United States (n = 9), Italy (n = 4), United Kingdom (n = 3), China (n = 3), India (n = 3), Iran (n = 2), Colombia (n = 2), Jordan (n = 1), Peru (n = 1), Hungary (n = 1), Guatemala (n = 1), Spain (n = 1), Mexico (n = 1), Pakistan (n = 1), and Turkey (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations